Knowledge-based expert system for predictive classification of main specific learning disabilities - R. M. Rasli; N. A. A. Aziz; S. A. Salim; F. M. Razali; N. M. Norwawi; Nurlida Basir (University of El Oued, 2024)
Conventional or the automation of computer-based screening and diagnosis is part of the methods that can assist to identify and detect these problematic students. However, several limitation or constraints have been identified leading towards the design and development of an innovative rapid web-oriented knowledge-based expert systems for predictive classification of five main types of specific learning disabilities namely dyslexia, dysgraphia, dyscalculia, dyspraxia and Attention Deficit Disorder/Attention Deficit Hyperactivity Disorder (ADD/ADHD). The result is displayed in a graphical form (chart and table) to make ease of understanding. This study is beneficial for parents, special education teachers, organizations and researchers by providing an alternative to the exclusion of redundant test and time saving for early screening of specific learning disabilities.